Desenvolvimento de modelo de gestão para empreendimento de economia solidária baseado na agricultura familiar para promover o desenvolvimento territorial sustentável na confecção de produtos de bambu - Tedeschi, Samara Pereira (2017)
Bamboo is a graminaceous plant with diverse possibilities of use that go from feeding to replacement of wood due to its physical and mechanical proprieties. Since such plant is perennial, its cultivation and handling, if performed correctly, can be an opportunity of exploring commercially the material. Since the sixties, the Brazilian government has encouraged silviculture through credit and funding programs to rural producers and in 2011 it was sanctioned the National Politics of Sustainable Handling and to the Cultivation of Bamboo (PNMCB, in Portuguese), stimulating the cultivation of the graminaceous plant by family farmers. Family Farm was created with the purpose of stimulating the cultivation of food by people who were given land rights by Brazilian Agrarian Reform to supply cities and PNMCB may be an alternative to stimulate the diversification of products. Solidary Economy can be a way of organization, generation of earnings, and decrease of poverty to family agriculturists, for it presents a self-managing, horizontal, cooperative, and solidary management structure, in which everyone involved display the same rights and duties, composing a collective enterprise. As an enterprise, it is possible to explore more deeply the marketplace through the sale of differentiated products, thus the concept of Sustainable Territorial Development can assist in competitiveness, earnings increase, besides stimulating the bamboo culture by means of the relations among the actors involved in the same productive chain. Therefore, the general objective of this research is to propose a management model to Solidary Economy Enterprises that are based on Family Farm to promote Sustainable Territorial Development in the confection of bamboo products. To develop the External Dimension that influence the enterprise was used the authors: Buarque (1999), Silva and Batalha (2011), Aaker (2012), and to the Internal Dimensions, was used the authors: GEPAI (2004), Aaker (2012) and the Solidary Economy concepts. The methodology of this research consists of using data collection instruments, such as document reading, searches in data, patents, and government agencies bases, interviews to verify the proposed management model. Also as subsidy to the elaboration of the model it was performed an Organizational Diagnosis to analyze the strong and weak points of the enterprise, based on the involved Internal and External Dimensions and the Organizational Planning to analyze opportunities for the development of the enterprise and identify competitive advantages by means of studying scenarios. The analysis of the External Dimensions allowed recognizing the external influences to the enterprise and its forms of access that allow the development, considering from the economic scenario to public, environmental, social, and technological politics. The analysis of the Internal Dimensions presented in the form of management modules granted the reflection on the formalization of existent information in the enterprise together with the recognition of points to be explored competitively and point to be revalued. With the accomplishment of the study of scenarios through crossing the proposed Dimensions, it was possible to visualize probable future situations that can assist as information for a Strategical Planning, leading a better positioning in marketplace. With this research, we concluded that is possible to identify the deficiencies of a family farm enterprise and, with the proposed model, the knowledge can be gained by farmers, making possible a better organization, management, and especially the identification of competitive advantages for the sector of bamboo.